Fine‐Scale Geothermal Heat Flow in Antarctica Can Increase Simulated Subglacial Melt Estimates. Issue 15 (14th August 2022) - McCormack, Felicity S.; Roberts, Jason L.; Dow, Christine F.; Stål, Tobias; Halpin, Jacqueline A.; Reading, Anya M.; Siegert, Martin J.
Abstract: Antarctic geothermal heat flow (GHF) affects the thermal regime of ice sheets and simulations of ice and subglacial meltwater discharge to the ocean, but remains poorly constrained. We use an ice sheet model to investigate the impact of GHF anomalies on subglacial meltwater production in the Aurora Subglacial Basin, East Antarctica. We find that spatially‐variable GHF fields produce more meltwater than a constant GHF with the same background mean, and meltwater production increases as the resolution of GHF anomalies increases. Our results suggest that model simulations of this region systematically underestimate meltwater production using current GHF models. We determine the minimum basal heating required to bring the basal ice temperature to the pressure melting point, which should be taken together with the scale‐length of likely local variability in targeting in‐situ GHF field campaigns. Plain Language Summary: Geothermal heat flow (GHF) is important in controlling both the ice temperature and the production of meltwater at the base of the Antarctic Ice Sheet, which impacts how rapidly ice flows. However, GHF estimates are generally low resolution and highly uncertain. This uncertainty in GHF impacts the reliability of model simulations of the flow of ice and meltwater into the ocean, which in turn impacts estimates of the contribution of ice sheets to future sea level rise. We use an ice sheet model to investigate how spatial variations in GHF impact meltwater production in the Aurora Subglacial Basin (ASB), East Antarctica. GHF fields with spatial variations lead to consistently higher melt rates at the ice sheet base than a constant GHF field with the same mean value. We determine the minimum heat at the ice sheet base in the ASB required to cause the ice to melt, and highlight regions where small variations in GHF will have greater impacts on ice melting. These results show where measurements to constrain GHF should be prioritized to improve ice sheet model simulations. Key Points: We present simulations of subglacial melt in the Aurora Subglacial Basin using various geothermal heat flow (GHF) fields Spatially‐variable GHF enhances simulated subglacial melt compared with constant GHF We highlight where GHF measurements should be prioritized for improved estimates of subglacial melt